Model Pengelolaan Ekonomi Pesantren dalam Mewujudkan Kemandirian Ekonomi di Pondok Pesantren Tanwirul Islam Sampang - Nurul Komariyah; Alan Su’ud Ma’adi (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Pesantren economics is an economic concept where pesantren manages and develops businesses with various innovations that can specifically benefit Islamic boarding schools and benefit the community in general in realizing economic independence. The purpose of this study is to find out the economic management model of the pesantren applied by the Tanwirul Islam Sampang Islamic boarding school and to find out the challenges faced by the Tanwirul Islam Sampang Islamic boarding school in managing the pesantren economy to realize economic independence. This type of research uses a qualitative descriptive approach, with data collection techniques in the form of interviews, observations, and documentation related to economic management at the Tanwirul Islam Sampang Islamic Boarding School. The results of the study show that the Tanwirul Islam Islamic boarding school implements the pesantren economic management model with an alumni-based economic development model, by utilizing the potential of alumni for the management of the pesantren business unit and implementing an entrepreneurship curriculum at the formal education level of students and involving external parties such as the surrounding community.